2016
DOI: 10.1371/journal.pone.0165258
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Cytotoxic, Genotoxic and Clastogenic Potential of Attalea phalerata Mart. ex Spreng. Oil Pulp In Vitro and In Vivo Experimental Models

Abstract: Attalea phalerata Mart. ex Spreng. (Arecaceae), popularly known as “bacuri”, is used in Brazilian folk medicine. Its oil is used orally to relieve pulmonary congestion and joint pain. In topical applications, it is applied as an effective hair tonic and anti-dandruff. The in natura pulp and its nuts are used as food because of its nutritional value. Despite its use in folk medicine, there is a lack of data regarding its in vivo/in vitro cytotoxic/genotoxic and clastogenic effects. Therefore, in this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
0
12
0
1
Order By: Relevance
“…A previous study with APOP in the same experimental model [ 3 ] did not present cytotoxicity in doses higher than that used in this study; However, the cells used were T84 (colon carcinoma). Thus, the difference between the results obtained can be attributed to the particularity of the cells in each study.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…A previous study with APOP in the same experimental model [ 3 ] did not present cytotoxicity in doses higher than that used in this study; However, the cells used were T84 (colon carcinoma). Thus, the difference between the results obtained can be attributed to the particularity of the cells in each study.…”
Section: Resultsmentioning
confidence: 72%
“…The pulp of "bacurizeiro" fruits are important foods for animals such as agouti, wild boars, macaws, parakeets, besides serving as raw material for starch development [ 1 , 2 ]. The high nutritional value of the fruit presents a promising nutraceutical food due to the presence of beneficial minerals, high amount of lipids, most of which are short chain saturated fatty acids and unsaturated fatty acids in addition to the presence of provitamin A carotenoids [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that oral administration at doses ranging from 125 to 2000 mg·kg −1 of the pulp oil of A. phalerata rats did not show any signs of toxicity and that the oil was considered safe in the doses evaluated [ 32 , 33 ]. According to our results, the intake of APNO (30.68% oleic acid, MUFA) can be considered safe for hepatic health, since studies have shown that MUFA-rich olive oil is considered a source lipid function that best preserves the liver during the aging process [ 34 ] and recovers the liver with hepatic steatosis [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, in accord to Lima et al (2018) are attributed to the Bacuri oil an antiinflammatory property that promote health, the fruit it's therefore a promising functional food, like the oil that have fitoterapic properties with no toxicity at the tested (Lima et al, 2016;Lima et al, 2017). They also have carotenoids; they are natural dyes that are present in natural products in general being considered bioactive compounds capable of promoting health like being against oxidative stress and preventing chronic disorders.…”
Section: Introductionmentioning
confidence: 81%